Testimony before judiciary as element in crime of false testimony "A comparative study" - Sawali, Mohab Ayman (Journal of Economic, Administrative and Legal Sciences, 2022)
This study dealt with the issue of testimony before the judiciary as an element in the crime of perjury, of particular importance from a practical point of view, in light of the application of Penal Code No. 74 of 1936 on the Gaza Strip until now. It was issued in the era of the British Mandate over Palestine. This is because the Public Prosecution Office in the Gaza Strip, and then the judiciary, adapt the texts of the articles related to the crime of perjury, in contrast to the correct interpretation of it, which is inconsistent with the English original. As a result, I worked on writing these words in order to clarify the true picture of some aspects of this crime. It was a summary of this modest effort to show that what is meant by testimony as an element in the crime is to testify before the judiciary, the public prosecution and the judicial control authorities. In order to reach this result, I followed a comparative approach between the Egyptian Penal Code and the Palestinian Penal Code, and guided by the Egyptian law in solving this problem, which I dealt with in two sections; The first of them was devoted to discussing the subject of the legally considered certificate. Then I devoted the second topic to the study of the body against which the false testimony is considered, and then I ended this study with a conclusion that included a set of results and recommendations.
Keywords: martyrdom; justice; perjury